Indigenous Substitutes for "Lignum Vitae" for Making Stern Bearings for Fishing Boats - VELD, M.; SIVADAS, T. K. (Fishery Technology, 2025)
Difficulties are very often encountered in selecting propermaterial for making stern bearings for fishing boats. Conventionalmaterials such as white metal, bronze etc. wear out too fast alsocausing considerable wear to the propeller shaft. Lignumvitae, anatural wood commonly used for this purpose, is not available on acommercial scale in our country. Results of trials carried out tofind out suitable substitutes for lignum-vitae from among indigenoustimbers are presented in this paper.